High‐resolution proteome maps of Bacillus licheniformis cells growing in minimal medium. Issue 15 (12th May 2015) - Voigt, Birgit; Albrecht, Dirk; Sievers, Susanne; Becher, Dörte; Bongaerts, Johannes; Evers, Stefan; Schweder, Thomas; Maurer, Karl‐Heinz; Hecker, Michael
<x xml:space="preserve">Abstract</x> Bacillus licheniformis is an important host for the industrial production of enzymes mainly because of its ability to secrete large amounts of protein. We analyzed the proteome of B. licheniformis cells growing in a minimal medium. Beside the cytosolic proteome, the membrane and the extracellular proteome were studied. We could identify 1470 proteins; 1168 proteins were classified as cytosolic proteins, 195 proteins with membrane‐spanning domains were classified as membrane proteins, and 107 proteins, with either putative signals peptides or flagellin‐like sequences, were classified as secreted proteins. The identified proteins were grouped into functional categories and used to reconstruct cellular functions and metabolic pathways of growing B. licheniformis cells. The largest group was proteins with functions in basic metabolic pathways such as carbon metabolism, amino acid and nucleotide synthesis and synthesis of fatty acids and cofactors. Many proteins detected were involved in DNA replication, transcription, and translation. Furthermore, a high number of proteins employed in the transport of a wide variety of compounds were found to be expressed in the cells. All MS data have been deposited in the ProteomeXchange with identifier PXD000791 (http://proteomecentral.proteomexchange.org/dataset/PXD000791).